Effect of Isolate Catechin GMB4 in Expression of GRP78 and Tunel Assay in Rat Cataract Model - Nugraha Wahyu Cahyana (Journal of Global Pharma Technology, 2020)
AbstractThis research is to explore glucose-regulated protein 78 (GRP78) expression and Tunel assay, signs of stress of endoplasmic reticulum (ER) and apoptosis in rat cataract model. Cataract was formed by inducing a subcutaneous injection of 19 µmol/kg sodium selenite to ten-day-old Wistar rats. The neonatal rats were divided into five groups randomly (n=5 in each group): a control group, and four cataract-induction groups, treated with either 0, 50, 100, 200 mg/kg catechin Isolate From GMB4 Clone Green Tea. We performed slit-lamp biomicroscopic analysis, immunohistochemistry for GRP78 and Tunel. Both eyes of all rats in Group 1 did not exhibit cataract formation. In Group 2, one out of five (20%) developed grade 3 cataracts and the remaining four out of five (80%) developed grade 4 cataracts. The grade of cataract formation decreased in groups 3, 4 and 5. The diﬀerence in exhibited cataract in the lens of all rats between Group 2 and any eyes of groups 3 or 4 and 5 were significant (P = 0.022, 0,001, 0,001). The mean amount of Tunel cells and GRP78 of group II rats were significantly (P < 0.01) higher than the levels in Group I, Group III, Group IV and Group V. Stress of Endoplasmic reticulum and apoptosis in the lens that increased following cataract formation in rats was suppressed by catechin Isolate From GMB4 Clone Green Tea.